2021
DOI: 10.1002/adma.202005477
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Spiky Peroxidase‐Mimics for Localized Bacterial Capture and Synergistic Catalytic Sterilization

Abstract: Nature has created an efficient sterilization model, i.e., the in situ bacterial capture and killing process via bacteriophages. The bacteriophage is a virus with a unique spiny tail foot; in general, it can capture bacteria and subsequently release nucleic acid to achieve replication and kill bacteria. We define this two-steps process as the localized "capture and killing" (LCK) action. Therefore, it is believed that this bioinspired LCK action may provide massive possibilities for developing efficient disinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 59 publications
0
105
0
Order By: Relevance
“…[25,26] Recently, many types of ROS catalytic nanoagents have been found to show efficient catalytic activity for the CDT process, like noble metal Pd nanomaterials, metal oxides, and metalorganic frameworks. [20,[27][28][29][30][31][32] At present, the semiconductor materials (e.g., TiO 2 ) and conjugated organic structure (e.g., porphyrin) are the main materials that can be utilized to integrate CDT, SDT, and PDT in one nanoplatform. However, the CDT efficiency of TiO 2 -based semiconductor materials is relatively low.…”
mentioning
confidence: 99%
“…[25,26] Recently, many types of ROS catalytic nanoagents have been found to show efficient catalytic activity for the CDT process, like noble metal Pd nanomaterials, metal oxides, and metalorganic frameworks. [20,[27][28][29][30][31][32] At present, the semiconductor materials (e.g., TiO 2 ) and conjugated organic structure (e.g., porphyrin) are the main materials that can be utilized to integrate CDT, SDT, and PDT in one nanoplatform. However, the CDT efficiency of TiO 2 -based semiconductor materials is relatively low.…”
mentioning
confidence: 99%
“…Our group recently found two other different reaction mechanisms for the H 2 O 2 assisted generation of •OH radicals. [55,56] In one report, as shown in Figure 2B, we found that the Pd-single-atom coordinated biocatalysts with a Pd-N catalytic center could generate two •OH radicals by DFT calculation. The H 2 O 2 adsorbs onto the Pd atom's active site first, then *H 2 O 2 will spontaneously remove an •OH.…”
Section: Catalytic Mechanismsmentioning
confidence: 79%
“…[ 12 ] Different types of noble metal NPs, such as Au, Ag, platinum group metals (Pd, Pt, Ru, Rh, Os, Ir), and their alloy NPs, have been widely used in different fields, including sensing, biomedicine, and catalysis. [ 104–112 ]…”
Section: Engineering Biocatalytic and Antioxidant Nanostructures: Rational Design And Catalytic Activitiesmentioning
confidence: 99%